Communicating Climate Change: A Qualitative Study Exploring how Communicators and Educators are Approaching Climate-Change Discussions - Katie Rohling; Cassie Wandersee; Lauri M. Baker; Peter Tomlinson (Journal of Applied Communications, 2016)
The scientific community has come to the conclusion that the climate is changing, but the existence of climate change continues to be rejected or doubted, creating communication challenges for professionals. The purpose of this study was to determine how education and communication professionals involved in climate-change communication are framing the discussions about climate change with agricultural producers. Semi-structured phone interviews were conducted to address terminology usage, challenges encountered, overcoming challenges, and utilization of social media when educating and communicating about climate change. Responses from professionals indicated: 1) they do not avoid using the term “climate change” but are concerned about jargon in materials; 2) the majority agreed the public believes climate change is happening; 3) not addressing the root causes of climate change; 4) framing messages; 5) addressing adaption options using local data; and 6) climate organizations are promoting materials on social media. This study recommends practitioners frame conversations depending on the audience and avoid using terminology that is not accepted by the target audience. Future research should investigate the effectiveness and uses of social media to engage desired audiences.
Keywords: Climate Change; Communication; Educational Materials; Social Media; Terminology